Preparing Pre-Service STEM Teachers in an Emerging Global Environment - Abah Joshua Abah; Iji Clement Onwu; Chinaka Taurayi Willard (Discourse and Communication for Sustainable Education)
The dynamics of Science, Technology, Engineering and Mathematics (STEM) teacher preparation has changed very dramatically in line with present-day realities and the demands of the emerging global environment. This work explores in detail the exigencies of global issues as they influence STEM education with specific attention given to 21st century skills, impact of technology, mathematics competencies, climate change, global competencies, and equity, diversity and inclusiveness. The article canvases for novel approaches to preparing STEM teachers who are skilled and knowledgeable practitioners, culturally aware, know about world events and global dynamics, literate for the 21st century, collaborative team members, effective users of technology and media, and responsible and ethical citizens. Recommendations on the knowledge, skills and attitudes that STEM teacher preparation should project were also given.